Anotações Interativas de Áudio Espacial em Vídeos 360° - Jony Ricardo Mesquita Xavier Costa (2019)
One of the new challenges to video directors that arose with the advent of the 360º video is that, differently from traditional video, the spectator has the freedom to look at wherever he or she wishes to inside the immersed 360° ambient, thus allowing the possibility of some important parts of the video be missed. The use of sound or visual virtual cues edited over the video is a way that is used to call for the spectator's attention and the audio ones have showed a good efficiency with that task, however its use may also lead to an opposite result and diminish the immersiveness experienced by the spectator or induce to fatigue and discomfort,  depending on how they are used. In addition, there is no spatial audio editor available for 360º videos that is affordable and easy to use. The purpose of this dissertation is, with the use of an intuitive and easy to use spatial audio annotation editor for 360° videos which supports annotation interactiveness with the spectator's movements, to conduct the user attention in an efficient and non intrusive way, in addition to strengthening the immersion sensation into the video environment. For such purpose, a web based prototype was developed, the prototype is able to create spatial audio annotations that can perceive the spectator's field of view in running time and fit themselves to some established rules plus the capacity of changing the video's ambient sound. Lastly some test ambients were created and two videos containing interactive audio annotations were presented with and/or without the annotations to 26 volunteers, who afterwards answered a questionnaire. The experiment was also videotaped for further analysis of the reactions to the stimuli. The results showed that the interactive audio hints have an efficient effect over the attention guiding and over the ambient perception on the videos' scenes, it was also noticed that the interaction with the spectator's movements had an effect by reducing the incidence of annotations.